Green Hero: Mobile Environmental Awareness Campaign for Children Using Gamification Approach - Ikmal Hisham, Muhammad Aidil Eiman; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2023)
Today’s technology has been innovated to a various number, encompassing in every aspect of daily life. Gamification is one the technique that has been used widely in the technology domain, which is a way of injecting game-elements into a nongaming system with intention of increasing the users interest and engagement. Despite the qualities poses by it, most sector does not grasp the advantage by implementing the technology especially in the educational sector. Issues such as environmental crisis that are lacking in awareness have yet to be integrated with the technique mentioned. Hence, Green Hero is an initiative taken to merge the environmental issues rising with the gamification method towards the children ranging from 10 to 12 years old since the current syllabuses have less focus on the importance of preserving the earth. Green Hero is expected to raise the awareness of the children towards the significance of concerning the environment.